2020
DOI: 10.3390/f11090905
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Effects of Genotype and Environment on Growth and Wood Features of Balfourodendron riedelianum Trees by Common Garden Experiments in Brazil

Abstract: Intraspecific studies with populations replicated in different sites allow the effects of genotype and environment on wood features and plant growth to be distinguished. Based on climate change predictions, this distinction is important for establishing future patterns in the distribution of tree species. We quantified the effects of genotype and environment on wood features and growth of 30-year-old Balfourodendron riedelianum trees. We used three provenances planted in two common garden experiments with diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…A functional advantage of thicker-wall fibers in the wood of taller trees of "tamboril" grown in eutrophic soil is to reinforce weakness areas, such as those close to the vessels [41]. Our findings demonstrated that fiber wall thickness was positively correlated to vessel diameter, suggesting that the thickening of the fiber walls would form in secondary xylem a matrix of fibers protecting the vessels of possible drought-induced negative pressure [42].…”
Section: Wood Anatomy In Response To Soil Typementioning
confidence: 59%
“…A functional advantage of thicker-wall fibers in the wood of taller trees of "tamboril" grown in eutrophic soil is to reinforce weakness areas, such as those close to the vessels [41]. Our findings demonstrated that fiber wall thickness was positively correlated to vessel diameter, suggesting that the thickening of the fiber walls would form in secondary xylem a matrix of fibers protecting the vessels of possible drought-induced negative pressure [42].…”
Section: Wood Anatomy In Response To Soil Typementioning
confidence: 59%
“…Toluidine blue staining was applied to the slides of the cross‐sections for 30 minutes, followed by photography. ImageJ software was utilized to process and analyze the images, quantifying anatomical traits (Figure S2) such as vessel density (VD) (Cai et al, 2013), vessel diameter (DV) (Silva et al, 2020), conduit wall span (b) (Hacke et al, 2001), and vessel wall thickness (t) (Hacke et al, 2001). Moreover, using ImageJ software, additional morphological traits, including leaf thickness, upper and lower epidermal thickness, palisade tissue thickness, and spongy tissue thickness were measured.…”
Section: Methodsmentioning
confidence: 99%